Strategic risk management: how can executives and the board effectively manage major risks? - Bromiley, Philip (Henry Stewart Talks, 2012)
Differences between problems, risk and uncertainty, Different meanings of risk management, Traditional risk management, Regulatory compliance, Enterprise risk management (ERM), Coping with major events, Implementing ERM, Total Quality Management (TQM) as risk management, Uses and abuses of sophisticated risk models, Fine tuning to disaster, Markets and firm risk-taking, Visible versus less visible performance indictors, Business killing uncertainties, Scenario analysis, Organizational resilience